1993
DOI: 10.2307/1131458
|View full text |Cite
|
Sign up to set email alerts
|

Theory-Based Correlations and Their Role in Children's Concepts

Abstract: Recent accounts of conceptual development have emphasized the important role intuitive theories play in concept formation; however, it is still not clear exactly how these theories exert their influence. We present evidence that elementary school age children use theories to link together specific features associated with individual concepts. The results of our first experiment indicate that theory-based correlations play a prominent role in typicality judgments and in decisions about category membership. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 0 publications
3
31
1
Order By: Relevance
“…Research in this area points to complex interactions between linguistic and non-linguistic input while children learn word meaning (e.g., Barrett, Abdi, Murphy, & Gallagher, 1993;Gelman, 1988;Jones & Smith, 1993). Because of the simplifications in the way the network was trained, it is not appropriate to use it to simulate developmental data.…”
Section: Network Architecturementioning
confidence: 99%
“…Research in this area points to complex interactions between linguistic and non-linguistic input while children learn word meaning (e.g., Barrett, Abdi, Murphy, & Gallagher, 1993;Gelman, 1988;Jones & Smith, 1993). Because of the simplifications in the way the network was trained, it is not appropriate to use it to simulate developmental data.…”
Section: Network Architecturementioning
confidence: 99%
“…Thus some researchers have suggested that children's naive theories might be generated by domain-specific modules (Leslie, 1994; Scholl & Leslie, 1999) or innate concepts in core domains (Carey & Spelke, 1994; Keil, 1995), while other NAÏVE THEORIES, AMBIGUOUS EVIDENCE Page 4 researchers have focused on children's ability to learn causal relations from statistical evidence (Gopnik et al, 2004;Gopnik, Sobel, Schulz, & Glymour, 2001;Schulz & Gopnik, 2004; Shultz & Mendelson, 1975; Siegler & Liebert, 1975; Sobel, Tenenbaum, & Gopnik, 2004; Watson & Ramey, 1972). Although some research on the development of scientific reasoning has emphasized the importance of integrating domain-specific knowledge with domain-general strategies (Barrett, Abdi, Murphy, & Gallagher, 1993; Klahr & Dunbar, 1988; Koslowski, 1996; Koslowski, Okagaki, Lorenz, & Umbach, 1989; Pazzani, 1991; Penner & Klahr, 1996; Schauble, 1990), those studies have focused primarily on adolescents and adults. Surprisingly little research has looked at how prior theories and evidence interact in young children's causal learning.…”
mentioning
confidence: 99%
“…This possibility is especially likely in situations where children can interact with the materials in ways that do not require the desired encoding (Uttal, O'Doherty, Newland, Hand, & DeLoache, 2009). Findings from numerous domains indicate that learners often fail to encode relevant dimensions, that inadequate encoding impairs learning, and that instructions that improve encoding of key features or relations improve learning (Alibali, 1999;Barrett, Abdi, Murphy, & Gallagher, 1993;Blaxton, 1989;Brown, Kane, & Echols, 1986;Chi, 1978;McCloskey & Kaiser, 1984;Ornstein et al, 1998;Siegler, 1976;Siegler & Chen, 1998;Staszewski, 1988). Thus, the cognitive alignment framework posits that there is a need, even with the best designed learning materials, for activities that direct learners' behaviors in ways that promote the encoding of the features relevant to the desired mental representation.…”
mentioning
confidence: 99%